In vitro regeneration of ‘carrick’ pear from leaf explants - SILVA, Carina Pereira da; PETERS, José Antônio; PASA, Mateus da Silveira; DANIELOWSKI, Rodrigo; BIANCHI, Valmor João (Revista Teste SPGG, 2017)
The aim of the present study was to investigate a two-step protocol as well as the effect of two types of cytokinins in the pretreatment and shoot induction media on in vitro adventitious shoot regeneration of pear leaf explants of ‘Carrick’ pear. Fully expanded healthy leaves were explanted onto shoot induction medium (SIM) following a pretreatment in liquid medium (PLM). Both media were supplemented with thidiazuron (TDZ) or 6-benzyladenine (BA) (PLM: 2 mg dm-3; SIM: 3 mg dm-3). The two-step protocol PLM [BA] + SIM [TDZ] is efficient for in vitro adventitious shoot regeneration from leaves of ‘Carrick’ pear.